Transformation of the motif of puppetry in the works of N.S. Leskov 1880-1890s (Eurasian Journal of Humanities and Social Sciences, 2022)
The article discusses the motives of puppet theater in the works of NS Leskov in 1880-1890. In order to cover the topic of the article, the research work of art critics of this period was used